Metabolically Engineered Escherichia coli for Conversion of D-Fructose to D-Allulose via Phosphorylation-Dephosphorylation - Guo, Qiang; Liu, Chen-Yang; Zheng, Ling-Jie; Zheng, Shang-He; Zhang, Ya-Xing; Zhao, Su-Ying; Zheng, Hui-Dong; Fan, Li-Hai; Lin, Xiao-Cheng (Frontiers in Bioengineering and Biotechnology, 2022)
D-Allulose is an ultra-low calorie sweetener with broad market prospects. As an alternative to Izumoring, phosphorylation-dephosphorylation is a promising method for D-allulose synthesis due to its high conversion of substrate, which has been preliminarily attempted in enzymatic systems. However, in vitro phosphorylation-dephosphorylation requires polyphosphate as a phosphate donor and cannot completely deplete the substrate, which may limit its application in industry. Here, we designed and constructed a metabolic pathway in Escherichia coli for producing D-allulose from D-fructose via in vivo phosphorylation-dephosphorylation. PtsG-F and Mak were used to replace the fructose PTS for uptake and phosphorylation of D-fructose to fructose-6-phosphate, which was then converted to D-allulose by AlsE and A6PP. The D-allulose titer reached 0.35 g/L and the yield was 0.16 g/g. Further block of the carbon flux into the Embden-Meyerhof-Parnas (EMP) pathway and introduction of an ATP regeneration system obviously improved fermentation performance, increasing the titer and yield of D-allulose to 1.23 g/L and 0.68 g/g, respectively. The E. coli cell factory cultured in M9 medium with glycerol as a carbon source achieved a D-allulose titer of ≈ 1.59 g/L and a yield of ≈ 0.72 g/g on D-fructose.